Casas españolas y matrimonios afromayas en Mérida de Yucatán, siglo XVI - Campos García, Melchor (El Colegio de México, A.C., 2018)
Despite the royal laws prohibiting Africans from residing in Indian towns and the laws encouraging endogamic marriages within the same indigenous group, Spanish households were sites of multiethnic coexistence, where ecclesiastic agreements to respect the will of the bride and groom, the interest of the masters in increasing their number of servants and attitudes towards Christian marriage combined to encourage Afro-Maya marriages. This article analyzes the ethnic composition of Yucatán families and the factors that influenced quantitative trends towards Afro-Maya marriages during the formative years of the city of Mérida. Uprooted Africans and women taken from their indigenous communities formed the basis for new interethnic networks in urban spaces, giving rise to a new, “mulatto” Afro-Maya urban community.